Impact of aerosol and water vapour on SW radiation at the surface: Sensitivity study and applications - Obregón, Maria de los Angeles (2018)
This study provides a sensitivity analysis of the downwelling shortwave (SW) irradiance at the Earth's surface with respect to the aerosols and the water vapour. Aerosols are characterized by optical thickness (AOD) and single scattering albedo (SSA), while water vapour is quantified by precipitable water vapour (PWV). For this purpose, downwelling SW irradiances under cloud-free conditions and a wide range of AOD, SSA and PWV values are simulated using libRadtran radiative transfer code. Results show SW irradiance decreases as AOD or PWV increases or as SSA decreases. The general analysis also shows that the combined effect of these quantities is not just the sum of the individual effects. Based on the results, two models are proposed to estimate the effect of aerosols and water vapour on SW irradiance. The two models are validated through comparing their results with radiation measurements registered at nine stations around the world. Models using two and three quantities show differences lower than 3% in 84% and 88% of cases, respectively. This good performance indicates the reliability of the models to estimate the effect of aerosols and water vapour on SW irradiance when no radiation measurements exist, provided that aerosol and water vapour information is available.